Bhārata kā vaidhānika evaṃ rāshṭrīya vikāsa : san 1600 se san 1919 taka - Gurmukh Nihal Singh, b. 1895 (SAMP early 20th-century Indian books project ;, 1952)
Development of the legal system in India; historical account.